A third dimension in the mirror? How senior managers design products and organizations - Norbert Bach; Peter Galvin (Strategic Change, 2020)
Individual CEO characteristics may affect architectural choices through the application of managerial discretion. Systems such as organizations and their products are not purely driven toward modularity because of external forces. Individual CEO characteristics may constitute an additional dimension to established mirroring considerations that impacts both the choice of architecture and the correspondence between product and organization architectures.
Keywords: 300